Infected site-restricted Foxp3(+) natural regulatory T cells are specific for microbial antigens - Suffia, Isabelle J. (The Rockefeller University Press, 2006)
Natural regulatory T (T reg) cells are involved in control of the immune response, including response to pathogens. Previous work has demonstrated that the repertoire of natural T reg cells may be biased toward self-antigen recognition. Whether they also recognize foreign antigens and how this recognition contributes to their function remain unknown. Our studies addressed the antigenic specificity of natural T reg cells that accumulate at sites of chronic infection with Leishmania major in mice. Our results support the idea that natural T reg cells are able to respond specifically to foreign antigens in that they strongly proliferate in response to Leishmania-infected dendritic cells, they maintain Foxp3 expression, and Leishmania-specific T reg cell lines can be generated from infected mice. Surprisingly, the majority of natural T reg cells at the infected site are Leishmania specific. Further, we showed that parasite-specific natural T reg cells are restricted to sites of infection and that their survival is strictly dependent on parasite persistence.